The Architecture of Interaction between Visual Working Memory and Visual Attention - Bahle, Brett (J Exp Psychol Hum Percept Perform, 2018)
In five experiments, we examined whether a task-irrelevant item in visual working memory (VWM) interacts with perceptual selection when VWM must also be used to maintain a template representation of a search target. This question is critical to distinguishing between competing theories specifying the architecture of interaction between VWM and attention. The single-item template hypothesis (SIT) posits that only a single item in VWM can be maintained in a state that interacts with attention. Thus, the secondary item should be inert with respect to attentional guidance. The multiple-item template hypothesis (MIT) posits that multiple items can be maintained in a state that interacts with attention; thus, both the target representation and the secondary item should be capable of guiding selection. This question has been addressed previously in attention capture studies, but the results have been ambiguous. Here, we modified these earlier paradigms to optimize sensitivity to capture. Capture by a distractor matching the secondary item in VWM was observed consistently across multiple types of search task (abstract arrays and natural scenes), multiple dependent measures (search RT and oculomotor capture), multiple memory dimensions (color and shape), and multiple search stimulus dimensions (color, shape, common objects), providing strong support for the MIT.